A little red dot at z = 7.3 within a large galaxy overdensity - Schindler, Jan-Torge; Hennawi, Joseph F.; Davies, Frederick B.; Bosman, Sarah; Endsley, Ryan; Wang, Feige; Yang, Jinyi; Barth, Aaron J.; Eilers, Anna-Christina; Fan, Xiaohui; Kakiichi, Koki; Maseda, Michael; et al. (Nature astronomy, 2025)
The nature of ‘little red dots’ and their relation to other forms of accreting supermassive black holes remain an open question. Here we report the discovery of a little red dot at z = 7.3. It is attenuated by moderate amounts of dust, AV = 2.79 mag, and has an intrinsic bolometric luminosity of 1046.6 erg s−1 and a supermassive black hole mass of 5 × 108 M⊙. Most notably, this object is embedded in an overdensity of eight nearby galaxies, allowing us to calculate a spectroscopic estimate of the clustering of galaxies around little red dots. We find a little red dot versus galaxy cross-correlation length of r0 = 8 ± 2 h−1 cMpc, comparable to that of z ≈ 6 ultraviolet-luminous quasars. The resulting estimate of their minimum dark matter halo mass log10(M halo,min/M⊙ ) = 12.0 +0,8 -1,0 indicates that nearly all haloes above this mass must host actively accreting supermassive black holes at z ≈ 7, in strong contrast with the far smaller duty cycle of luminous quasars (<1%). Our results, taken at face value, motivate a picture in which supermassive black holes in little red dot phases could serve as the obscured precursors of ultraviolet-luminous quasars, which provides a natural explanation for the short ultraviolet-luminous lifetimes inferred from both quasar clustering and quasar proximity zones.